Approaches for estimating the degree of depression of a territory (a region) - Anna Chechel; Sergei Konoplyov (Cхід, 2014)
This study focuses on the definition of regions in post-industrial areas (Old Industrial Cities) and the method of cluster analysis as the technique for estimating the degree of depression of a coal region.